Environmental Approach in Problem-Based Learning: Its Effect on the Reflective Thinking Skills of Junior High School Students - Priadi, Median Agus; Maulina, Dina; Marpaung, Rini Rita T.; Conyta, Elvira; Suwandi, Tri (UNIVERSITAS ISLAM NEGERI RADEN INTAN LAMPUNG, 2026)
This study aimed to examine the effect of Problem-Based Learning (PBL) integrated with an environmental approach on junior high school students’ reflective thinking skills in the topic of interactions between living organisms and their environment. The research employed a quasi-experimental design with a pretest–posttest non-equivalent control group. A total of 72 seventh-grade students were selected through purposive sampling and divided into an experimental group and a control group. The experimental group received PBL with an environmental approach, while the control group was taught using conventional discovery learning. Data were collected using a descriptive test based on five indicators of reflective thinking: triggering event, exploration, integration, application of solutions, and reflection. The results showed that the experimental group achieved a higher N-gain score (0.66) compared to the control group (0.53), both categorized as moderate improvement. The independent samples t-test indicated a significant difference between the two groups (p < 0.05), with an effect size of 1.53, categorized as large. These findings suggest that PBL integrated with an environmental approach is effective in enhancing students’ reflective thinking skills through contextual and meaningful science learning. Pendekatan Lingkungan dalam Pembelajaran Berbasis Masalah: Pengaruhnya terhadap Kemampuan Berpikir Reflektif Siswa Sekolah Menengah Pertama ABSTRAK: Penelitian ini bertujuan untuk menganalisis pengaruh model Problem-Based Learning (PBL) yang berorientasi pada pendekatan lingkungan terhadap kemampuan berpikir reflektif pada materi interaksi makhluk hidup dan lingkungannya. Penelitian menggunakan desain kuasi eksperimen dengan bentuk pretest–posttest non-equivalent control group. Sampel terdiri dari 72 siswa kelas VII yang dipilih melalui teknik purposive sampling dan dibagi ke dalam kelas eksperimen dan kelas kontrol. Kelas eksperimen diberi perlakuan berupa PBL berbasis pendekatan lingkungan, sedangkan kelas kontrol menggunakan pembelajaran discovery learning. Instrumen penelitian berupa tes uraian yang berdasarkan lima indikator berpikir reflektif, yaitu triggering event, eksplorasi, integrasi, aplikasi solusi, dan refleksi. Hasil penelitian menunjukkan bahwa nilai N-gain kelas eksperimen sebesar 0,66 lebih tinggi dibandingkan kelas kontrol sebesar 0,53, yang keduanya termasuk kategori sedang. Uji independent sample t-test menunjukkan adanya perbedaan signifikan (p < 0,05), dengan nilai effect size sebesar 1,53 (kategori besar). Hal ini menunjukkan bahwa PBL berbasis pendekatan lingkungan meningkatkan kemampuan berpikir reflektif siswa melalui pembelajaran kontekstual dan bermakna.